Actividades del profesional en enfermería para educar sobre el riesgo en el embarazo adolescente a las estudiantes de 10mo y 1ero de bachillerato de la Unidad Educativa Eugenio Espejo, Babahoyo-Los Ríos, octubre 2018- abril 2019 - Ochoa Acosta, Cindy Cicinia (2019)
The present thesis refers to the activities of the nursing professional to educate adolescent pregnancy risk students of 10th and 1st baccalaureate of the Educational Unit Eugenio Espejo, Babahoyo-Los Rios, October 2018-April 2019. which forms the objective of establishing the activities of the nursing professional to educate adolescents about the risk of adolescent pregnancy in the 10th and 1st baccalaureate students of the Educational Unit Eugenio Espejo -Babahoyo- Los Ríos, October 2018- April 2019. Through this research work through field research and using deductive method we will know the consequences of adolescent pregnancy as well as its main risk factors and how to help prevent this phenomenon of public health since according to results obtained in the investigation one of the main causes of adolescent pregnancy is the beginning of sexual activity at an early age without due protection, however it was also known that most of the adolescents investigated did not know the risks of teenage pregnancy.